Development Of Suburban Settlements In The Northern Ring Road Corridor, Tanjungbalai City - Richard Andeas Putra Marbun; Abdi Sugiarto; Cut Nuraini (Yayasan Sinergi Multidimensi Kreatif, 2025)
This study aims to examine the development of suburban settlements in the northern ring road corridor ofTanjungbalai City. This research uses a qualitative approach that aims to deeply understand the phenomenon ofsettlement development in the suburbs of Tanjungbalai. In this context, the case study is focused on thedevelopment of settlements in the North Ring Road Corridor, Tanjungbalai City. Data Collection Techniquessuggest that in-depth interviews are an effective technique for gathering qualitative information, explaining thatparticipatory observation helps researchers understand the social and cultural context in which the researchtakes place. Research results Significant population growth due to urbanization has increased the demand forhousing in the Northern Ring Road Corridor area. The development of settlements has led to significant changesin land use in this area. The rapid development of settlements has an impact on the environment, includingpollution and degradation of green open spaces. Although the development of settlements brings economicopportunities, people in the region face significant challenges related to quality of life. With awareness of thefactors that affect the development of settlements and their impact on the environment and people's lives, it ishoped that the planning and management of the North Ring Road Corridor area can be carried out in a sustainableand better manner in the future.